Effect of knowledge management on software product experience with mediating effect of perceived software process improvement: An empirical study for Indian software industry. (April 2020) - Chugh, Mitali; Chanderwal, Nitin; Upadhyay, Rajesh; Punia, Devendra Kumar
The software development industry is characterised by swift innovation and competition. To survive, software engineering (SE) organisations need to develop high-quality software products in a timely fashion and at low cost. Knowledge-based approaches to software development are extremely supportive to acquiring new knowledge and leveraging existing knowledge from software projects; this enables constant improvement of software development practices. In this empirical study of Indian SE organisations, we study the impact of managing knowledge for perceived software process improvement (PSPI) and its effect on software product quality. Information technology (IT) in knowledge management (KM) is an important facilitator for any SE organisation desiring to exploit evolving technologies for management of their knowledge assets and for carrying out various KM processes of knowledge capture, storage, retrieval and sharing. Surveys collected from Indian SE organisations were analysed to propose a model using a structured equation modelling (SEM) technique. Our findings reveal that the relation between KM and quality of software product is positively mediated by PSPI. These findings reinforce an arena that is of growing importance to researchers and practitioners and which has seen only a limited number of empirical studies to date in the context of Indian SE organisations.